(untitled) (ASEAN Engineering Journal, 2025)
In the context of modern industrial facilities, automation of production processes has become essential, offering cost reduction, operational efficiency, and minimized human involvement. A specific challenge arises from the conventional method of sorting unpicked bottles post- uncasing, leading to a high incidence of broken returnable bottles. To address this, we present the "Automated Sorting System of Cases with Unpicked Bottles," aimed at minimizing bottle breakage during manufacturing. Our objective is to enhance bottle preservation while achieving substantial cost savings and profitability. At the core of this system is its seamless integration into the conveyor network, enabling real-time bottle sorting as cases move towards the packer. Utilizing the Programmable Logic Controller working in conjunction with various sensors, including retro reflective and diffuse sensors, the system ensures responsive and precise operation. These sensors provide immediate feedback to a linked pneumatic cylinder, enabling it to respond according to preset settings and circumstances. Importantly, through extensive simulation and testing, we have achieved a remarkable reduction in bottle breakage rates. Our results indicate a reduction in breakage by up to 3800 bottles per day, attributed to the system's efficient and precise sorting capabilities. This innovative approach not only significantly improves process efficiency but also results in tangible cost savings, making it a highly cost- effective solution for the industry